2005
DOI: 10.1007/s11258-005-9071-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allelopathic compounds produced by Cistus ladanifer on germination of 20 Mediterranean taxa

Abstract: In order to analyze the extent to which allelopathic action of Cistus ladanifer may influence the successional progression towards Mediterranean sub-climacic shrublands and the geographical distribution of other species, the inhibitory effect of Cistus ladanifer extracts on the germination of 20 Mediterranean species was analyzed. Five of the species tested were characteristic of maquis sub-climacic shrublands: Arbutus unedo, Adenocarpus argyrophyllus, Phillyrea angustifolia, Phillyrea latifolia, and Rhamnus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 28 publications
(27 reference statements)
3
52
1
1
Order By: Relevance
“…These results are in agreement with optimal germination temperature for most Mediterranean shrub species ranging between 15 ºC and 20 ºC (Thanos et al 1992(Thanos et al , 1995. Alternating temperatures (20/7 ºC and 25/15 ºC) resulted in low germination percentages, although previous works stated that Phillyrea seeds germinated a 90% after 60 days at 20/7 ºC (Herranz et al 2006), or a 90%…”
Section: Discussionsupporting
confidence: 87%
“…These results are in agreement with optimal germination temperature for most Mediterranean shrub species ranging between 15 ºC and 20 ºC (Thanos et al 1992(Thanos et al , 1995. Alternating temperatures (20/7 ºC and 25/15 ºC) resulted in low germination percentages, although previous works stated that Phillyrea seeds germinated a 90% after 60 days at 20/7 ºC (Herranz et al 2006), or a 90%…”
Section: Discussionsupporting
confidence: 87%
“…A variation in seed germination requirements among populations also could explain the great differences found in germination response to temperature when compared to previous works. In our assay, germination at 20/10 ºC was 75%, while previous assays with P. angustifolia seeds collected in a different Spanish population obtained values of 10% germination at 20/7 ºC (Mira et al, 2015b) or values of 90% at 20/10 ºC or 20/7 ºC (García-Fayos et al, 2001;Herranz et al, 2006). Intraspecific variation in seed response to GA3 also could explain that while our data show that GA3 is detrimental to seed germination, previous results indicated that GA3 allowed high germination (Mira et al, 2015b).…”
Section: Discussioncontrasting
confidence: 47%
“…Los exudados secretados por las hojas de C. ladanifer mostraron actividad inhibitoria de la germinación de especies herbáceas, que no se encuentran normalmente en los jarales (Chaves et al, 1993;Chaves y Escudero, 1997;Chaves et al, 2001a;Chaves et al, 2001b;Chaves et al, 2003). Extractos acuosos de hojas de C. ladanifer se ensayaron frente a la germinación de 20 especies que normalmente comparten su hábitat (Herranz et al, 2006 En diferentes poblaciones de C. ladanifer se estudió la variación cuantitativa y cualitativa del exudado de sus hojas y tallos, incluyendo el contenido en geninas de flavonoides (Sosa et al, 2005). Fueron establecidos dos grupos de poblaciones, por las diferentes condiciones climáticas en que se desarrollaban.…”
Section: Cistus Ladanifer Lunclassified